PENERAPAN PENDEKATAN EMOSIONAL GURU DALAM MENGOPTIMALKAN PERAN AKTIF SISWA PADA PEMBELAJARAN FIKIH MUAMALAT KELAS X MAN 4 KARAWANG - Faisal, Muhamad; Rukajat, Ajat; Fahmi Arifudin, Yadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The teacher’s emotional approach is one of the efforts to create a comfortable learning atmosphere and support students’ active participation in Fiqh Muamalat learning. However, in its implementation, there are still students who are passive and lack self-confidence during the learning process. Based on preliminary observations at MAN 4 Karawang, teachers have attempted to apply an emotional approach in Fiqh Muamalat learning, but its implementation in optimizing students’ active participation still needs to be studied more deeply. This study aims to identify and describe the implementation of the teacher’s emotional approach, the supporting and inhibiting factors, and the results of its implementation in optimizing the active participation of tenth-grade students in Fiqh Muamalat learning at MAN 4 Karawang. This study employed a qualitative approach with a descriptive research type. The research subjects consisted of the Fiqh Muamalat teacher, tenth-grade students, and the principal. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used data reduction, data presentation, conclusion drawing, and data verification. The results showed that the teacher’s emotional approach was implemented through warm communication, motivation, appreciation, and the creation of a safe and comfortable learning environment. Supporting factors included facilities and infrastructure, teacher professionalism, and open communication, while inhibiting factors consisted of communication barriers and students’ family factors. The teacher’s emotional approach had a positive impact on students’ comfort, motivation, self-confidence, and active participation in Fiqh Muamalat learning. Thus, the teacher’s emotional approach plays an important role in optimizing the active participation of tenth-grade students at MAN 4 Karawang.